Уран в антропогенных карбонатах на территории Уфы; Записки горного института; Т. 260 - Фархутдинов И. М. Исхак Мансурович; Хайруллин Р. Р. Рустам Равильевич; Соктоев Б. Р. Булат Ринчинович; Злобина А. Н. Анастасия Николаевна; Чесалова Е. И. Елена Игоревна; Фархутдинов А. М. Анвар Мансурович; Ткачев А. В. Андрей Владимирович (2023, 2023)
Заглавие с экрана